Effectiveness of Foot Massage and Range of Motion Exercise on Diabetic Patients' Peripheral Neuropathy: A Randomized Controlled Trial - Al-Fahham, Taher Mohsin; Al-Jubouri, Mohammed Baqer; Al Omari, Omar (Iraqi National Journal of Nursing Specialties, 2024)
Objective(s): To determine which interventions: Foot massage, or Range of motion exercise, is most effective for diabetic peripheral neuropathy.Methods: A true experimental study was conducted from December 2, 2022, to April 25, 2023. A probability (simple random) sample of (77) diabetic patients diagnosed with peripheral neuropathy at Al-Hassan Specialized Center for Endocrinology and Diabetes, Karbala, Iraq. The study samples were randomly divided into three groups: 25 patients in the Foot massage group and 25 patients in the range of motion group, which received three sessions per week for two weeks, while 27 patients in the control group receive the routine care. Data was collected using Toronto Clinical Neuropathy Score to assess diabetic neuropathy. The data were analyzed using SPSS version 26, paired t-test, Analysis of Variance, Pearson correlation, least significant difference, and Friedman's test was used for the analyzing data in the current study.Results: The decrease in the Toronto Clinical Neuropathy Score level in both intervention groups was significant between the pretest and posttest (0.000). In comparison with the control group, there was a significant difference from the foot massage group (0.001) in the post-test. However, there was a non-significant difference in comparing the range of motion group with the control group in the post-test. According to Friedman's test mean rank, the most effective intervention group was a foot massage, which had the lowest mean.Conclusion: Although foot massage, and range of motion exercises are all supportive care techniques for diabetic patients with peripheral neuropathy, foot massage was more effective than range of motion exercises, and range of motion exercises were less effective at the peripheral neuropathy level. Recommendations: These techniques have supportive care when considering non-pharmacological interventions to improve diabetic peripheral neuropathy and prevent complications among diabetes patients.